Substantiation of methods for constructing engineering networks of operating industrial enterprises - Ishchenko, О.; Zhvan, V.; Dolgov, V. (Ways to Improve Construction Efficiency, 2019)
Industry is one of the most energy-intensive sectors of the economy, this sector has a rather large potential for energy saving. The process of formation of energy saving engineering systems of an industrial enterprise, which is subject to complex restoration, is an active system for implementing the energy saving function, since it applies solutions related to engineering networks and equipment. The article analyzes the methods for improving the energy efficiency of engineering systems and discusses the features of using energy-saving technologies when restoring engineering networks of existing industrial enterprises.